Real‐Time VCC Monitoring and Forecasting in HEK‐Cell‐Based rAAV Vector Production Using Capacitance Spectroscopy - Rafael Machleid; Suneetha Nunna; Ajith George; Jonas Austerjost; Magda Tomala; Izabella Surowiec (Engineering in Life Sciences)
ABSTRACT Recombinant adeno‐associated virus (rAAV) vector production is a complex process in which the robust cultivation of human embryonic kidney cells (HEK293) plays a critical role in generating high‐quality viral vectors. Tracking the viable cell concentration (VCC) during upstream production is essential for process monitoring and for implementing actions that ensure optimal process management. The advent of inline capacitance probes has introduced a crucial process analytical technology (PAT) tool for real‐time VCC measurement. Here, we present the development and application of a method for real‐time monitoring of VCC in HEK293‐based rAAV vector production. In a first step, BioPAT Viamass probes were used to record capacitance data of individual 10 L rAAV‐8 batches within a frequency range of 50 kHz–20 MHz. Based on the capacitance data, a linear single‐frequency model and an orthogonal partial least square (OPLS) multifrequency model for VCC prediction were developed. Subsequently, these models were deployed inline, and predictions were exposed into BioPAT MFCS bioprocess control software, enabling real‐time VCC monitoring in subsequent rAAV‐8 production batches. In addition, the continuous VCC signal was used as input for an exponential cell growth model that was deployed inline to provide accurate real‐time forecasting of the transfection time point. To the best of our knowledge, this is the first example of inline deployment of VCC and Time‐Till‐Transfection predictive models to the bioprocess control system for real‐time monitoring and forecasting of these parameters in HEK‐cell‐based transient rAAV vector production.